10 Quantitative myocardial perfusion and longitudinal strain by feature tracking in newly diagnosed, treatment naïve rheumatoid arthritis. (18th April 2016) - Fent, G; Garg, P; Dobson, L; Musa, T Al; Foley, J; Swoboda, P; Greenwood, J; Plein, S
Abstract : Objectives: Rheumatoid arthritis (RA) is associated with increased cardiovascular mortality. Proposed mechanisms include coronary microvascular dysfunction due to immune dysregulation and systemic inflammation. First pass myocardial perfusion CMR allows quantification of myocardial blood flow (MBF) and myocardial perfusion reserve (MPR). In the absence of coronary artery disease (CAD), reduced MPR represents coronary microvascular dysfunction. We hypothesised MPR would be reduced in RA and that abnormalities in left ventricular (LV) deformation would be evident in RA, as LV mass has been reported to be reduced in established disease. Methods: Twelve patients with newly diagnosed, treatment naïve RA and 12 healthy volunteers (HV) underwent CMR at 3.0T (Phillips Achieva TX). Both groups had no history of CAD. Dual bolus resting and stress perfusion imaging was performed (0.1mmol/kg Gadolinium DTPA) and MBF estimated for the mid ventricular slice using Fermi constrained convolution (PMI v 0.4 [Sourbron, 2009]). Left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) by feature tracking were calculated using bSSFP images (CVI 42, Circle Cardiovascular Imaging, Calgary, Canada). Results: Mean age of RA patients was 48 ± 16 and mean age of HV 47 ± 14. Of the RA patients, 4 were male and 8 female. Of the HV, 2 were male and 10 female. Mean MPR values were 1.98 ± 0.79 and 1.99 ± 0.72 (P = 0.88) for RA and HV respectively (Figure 1 ). Mean values for LVEF were 63 ± 4 and 62 ± 4% (P = 0.48) respectively for RA patients and HV. Mean values for GLS were −20.2 and −21 ± 0.4 (P = 0.396) for RA and HV respectively. Conclusion: These findings suggest treatment naïve RA patients have no detectable abnormalities on perfusion CMR. Therefore, whilst present in established RA, coronary microvascular dysfunction may not yet have developed in early RA. No abnormalities of LV systolic function were evident and may be a later manifestation of RA.